E. coli histidine triad nucleotide binding protein 1 (ecHinT) is a catalytic regulator of D-alanine dehydrogenase (DadA) activity in vivo. - Sanaa Bardaweel (Public Library of Science (PLoS), 2011)
Histidine triad nucleotide binding proteins (Hints) are highly conserved members of the histidine triad (HIT) protein superfamily. Hints comprise the most ancient branch of this superfamily and can be found in Archaea, Bacteria, and Eukaryota. Prokaryotic genomes, including a wide diversity of both gram-negative and gram-positive bacteria, typically have one Hint gene encoded by hinT (ycfF in E. coli). Despite their ubiquity, the foundational reason for the wide-spread conservation of Hints across all kingdoms of life remains a mystery. In this study, we used a combination of phenotypic screening and complementation analyses with wild-type and hinT knock-out Escherichia coli strains to show that catalytically active ecHinT is required in E. coli for growth on D-alanine as a sole carbon source. We demonstrate that the expression of catalytically active ecHinT is essential for the activity of the enzyme D-alanine dehydrogenase (DadA) (equivalent to D-amino acid oxidase in eukaryotes), a necessary component of the D-alanine catabolic pathway. Site-directed mutagenesis studies revealed that catalytically active C-terminal mutants of ecHinT are unable to activate DadA activity. In addition, we have designed and synthesized the first cell-permeable inhibitor of ecHinT and demonstrated that the wild-type E. coli treated with the inhibitor exhibited the same phenotype observed for the hinT knock-out strain. These results reveal that the catalytic activity and structure of ecHinT is essential for DadA function and therefore alanine metabolism in E. coli. Moreover, they provide the first biochemical evidence linking the catalytic activity of this ubiquitous protein to the biological function of Hints in Escherichia coli.